2018
DOI: 10.3892/etm.2018.6648
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of propofol in endometriosis and its mechanism

Abstract: Abstract. Endometriosis (EM) is a common benign gynecological disorder. The present study aimed to investigate the potential role of propofol, a commonly used intravenous anesthetic agent, in the pathogenesis of EM. The EM cell line CRL-7566 was used in the present study. CRL-7566 cells were first treated with various concentrations of propofol (0, 1, 5 or 10 µg/ml) for specific duration, and the cell viability and apoptotic rate were determined by performing an MTT and a flow cytometric cell apoptosis assay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…However, the function of propofol in the ectopic lesions of EM has not been investigated, which will be explored in the current study. More interestingly, during the conduction of our study, propofol is found to inhibit cell viability and induce cell apoptosis of EM (Feng and Sun 2018), which further indicated the inhibitory role of propofol in the progression of EM. Consistently, we found the inhibitory effects of propofol in EM, evidenced by the decreased cell proliferation and invasion of ESCs after propofol administration.…”
Section: Discussionsupporting
confidence: 65%
“…However, the function of propofol in the ectopic lesions of EM has not been investigated, which will be explored in the current study. More interestingly, during the conduction of our study, propofol is found to inhibit cell viability and induce cell apoptosis of EM (Feng and Sun 2018), which further indicated the inhibitory role of propofol in the progression of EM. Consistently, we found the inhibitory effects of propofol in EM, evidenced by the decreased cell proliferation and invasion of ESCs after propofol administration.…”
Section: Discussionsupporting
confidence: 65%
“…The cells were maintained in DMEM/F12 medium (Gibco; Thermo Fisher Scientific, Inc.) with 10% FBS (Gibco; Thermo Fisher Scientific, Inc.), 100 U/ml penicillinG and streptomycin sulfate (Invitrogen; Thermo Fisher Scientific, Inc.) in a humidified incubator with 5% CO 2 at 37˚C. For drug-toxicity assays, the cells were cultured in 6-well plates and exposed to different concentrations of propofol (0, 1, 5 and 10 µg/ml) for 48 h ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…Endometriotic cells could not express surface receptors to trigger proapoptotic proteins; neither apoptotic signals were appropriately transduced, leading to proliferation being triggered instead 188 . GnRH agonists, such as leuprolide acetate or the preclinical nonhormonal drug propofol, increased the levels of proapoptotic proteins, as well as decreased the levels of antiapoptotic proteins and promitogenic cytokines 52,100 . Melatonin is highly effective in amplification of apoptotic activity via regulating MMP‐3 signal, was able to regress EM at either early or late stage.…”
Section: Potential New Pharmaceuticals and Their Target‐signaling Pathwaysmentioning
confidence: 99%